The Diphosphorus Complex [Cp2Cr2(CO)4(η2‐P2)] as a Building Block in the Coordination Chemistry of Silver. Issue 15 (20th April 2018) - Elsayed Moussa, Mehdi; Welsch, Stephan; Gregoriades, Laurence J.; Balázs, Gábor; Seidl, Michael; Scheer, Manfred
Abstract : The reaction of the tetrahedral diphosphorus complex [Cp2 Cr2 (CO)4 (η 2 ‐P2 )] (Cp = C5 H5 ) (2 ) with Ag[AlOC(CF3 )3 4 ] (AgTEF) (3 ) leads to the formation of the Ag I dimer [Ag2 (η 2 ‐2 ) (η 1 ‐2 )(η 1 :η 1 ‐2 )2 ][TEF]2 (5 ). This dimer can be used as a suitable precursor for the synthesis of the unprecedented 1D organometallic‐organic hybrid polymer [Ag2 (η 1 ‐2 )2 (η 1 :η 1 ‐2 )2 µ, η 1 :η 1 ‐(C8 H4 N2 )] n [TEF]2n (8 ) upon its reaction with 1, 4‐dicyanobenzene (7 ). The driving force for this supramolecular assembly reaction is supported by DFT calculations. Abstract : The reaction of the diphosphorus complex [Cp2 Cr2 (CO)4 (η 2 ‐P2 )] (Cp = C5 H5 ) with Ag[AlOC(CF3 )3 4 ] results in an Ag I dimer, which is used as a suitable precursor for the synthesis of an unprecedented 1D organometallic‐organic hybrid coordination polymer upon its reaction with 1, 4‐dicyanobenzene.